Giúp mình với mấy bạn

Question

Giúp mình với mấy bạn
giup-minh-voi-may-ban

in progress 0
King 9 months 2021-04-20T16:06:16+00:00 1 Answers 19 views 0

Answers ( )

    0
    2021-04-20T16:08:08+00:00

    Đáp án:

     b) \(\left[ \begin{array}{l}
    x = k2\pi \\
    x = \arccos \dfrac{1}{6} + k2\pi \\
    x =  – \arccos \dfrac{1}{6} + k2\pi 
    \end{array} \right.\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    a)4{\cos ^2}x – 2\cos x – 2 = 0\\
     \to 2\left( {2\cos x + 1} \right)\left( {\cos x – 1} \right) = 0\\
     \to \left[ \begin{array}{l}
    \cos x =  – \dfrac{1}{2}\\
    \cos x = 1
    \end{array} \right.\\
     \to \left[ \begin{array}{l}
    x = \dfrac{{2\pi }}{3} + k2\pi \\
    x =  – \dfrac{{2\pi }}{3} + k2\pi \\
    x = k2\pi 
    \end{array} \right.\left( {k \in Z} \right)\\
    b)6{\sin ^2}x + 7\cos x – 7 = 0\\
     \to 6\left( {1 – {{\cos }^2}x} \right) + 7\cos x – 7 = 0\\
     \to  – 6{\cos ^2}x + 7\cos x – 1 = 0\\
     \to \left( {1 – \cos x} \right)\left( {6\cos x – 1} \right) = 0\\
     \to \left[ \begin{array}{l}
    \cos x = 1\\
    \cos x = \dfrac{1}{6}
    \end{array} \right.\\
     \to \left[ \begin{array}{l}
    x = k2\pi \\
    x = \arccos \dfrac{1}{6} + k2\pi \\
    x =  – \arccos \dfrac{1}{6} + k2\pi 
    \end{array} \right.\left( {k \in Z} \right)\\
    c)2{\sin ^2}x – 4\cos x\sin x – 3{\cos ^2}x =  – 2\\
     \to \dfrac{{2{{\sin }^2}x}}{{{{\cos }^2}x}} – \dfrac{{4\sin x}}{{\cos x}} – 3 =  – \dfrac{2}{{{{\cos }^2}x}}\\
     \to 2{\tan ^2}x – 4\tan x – 3 =  – 2\left( {1 + {{\tan }^2}x} \right)\\
     \to 4{\tan ^2}x – 4\tan x – 1 = 0\\
     \to \left[ \begin{array}{l}
    \tan x = \dfrac{{1 + \sqrt 2 }}{2}\\
    \tan x = \dfrac{{1 – \sqrt 2 }}{2}
    \end{array} \right.\\
     \to \left[ \begin{array}{l}
    x = \arctan \left( {\dfrac{{1 + \sqrt 2 }}{2}} \right) + k\pi \\
    x = \arctan \left( {\dfrac{{1 – \sqrt 2 }}{2}} \right) + k\pi 
    \end{array} \right.\left( {k \in Z} \right)
    \end{array}\)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )